Dukungan Keluarga terbukti Meningkatkan Kepatuhan Pembatasan Cairan Pasien Gagal Jantung - Iriantika, Purna Tugas; Kurniawati; Mukarromah, Indah; Hariyanto, Sufendi (Journal of Pubnursing Sciences, 2024)
Background: Compliance defined as the level of behavior of a person who receives treatment and implements a lifestyle in accordance with the recommendations of health care providers. In heart failure patients, fluid intake is strictly limited to prevent pulmonary edema. For this reason, family support is needed to help provide fluids to heart failure patients. Aim: To determine corelation between family support and compliance with fluid restrictions in heart failure patients. The research was conducted at Cardiac Pilyclinic in June 2024. Method: The research design is correlation analytic with cross-sectional methods. The population in all heart failure patients at the heart clinic of RSUD dr. R. Koesma Tuban as many as 384 people, and a sample of 80 people was obtained using a simple random sampling technique. The independent variable (family support) and the dependent variable (compliance). Analysis test uses the Chi Square Test. Results: The research results showed a ρ-value of 0.00 (α<0.05) so it was concluded that there was a corelation between family support and compliance with fluid restrictions in heart failure patients. Conclusion: By providing consistent and loving support, families can help patients remain adherent to treatment plans, improve health outcomes, and prevent complications that may arise from non- adherence.